MECHANISM OF CHEMICAL MUTAGENESIS IV. : Reaction between Triethylene Melamine and Nucleic Acid Components - Lorkiewicz, Z. (1961)
Lorkiewicz, Z. (University of Wisconsin, Madison), and Waclaw Szybalski. Mechanism of chemical mutagenesis. IV. Reaction between triethylene melamine and nucleic acid components. J. Bacteriol. 82: 195–201. 1961.—Triethylene melamine interacts primarily with phosphorylated intracellular deoxyribonucleic acid (DNA) precursors and not with DNA. It was found by direct chemical and chromatographic analysis that only pyrimidine precursors of nucleic acids are attacked by triethylene melamine. In the course of the triethylene melamine-deoxycytidine reaction the mutagenicity of the reaction mixture is lost, but the mutagenicity of the triethylene melamine-thymidine reaction products significantly increases above that of the reaction substrates. Several steps are postulated to explain the mechanism of the triethylene melamine-initiated mutagenic reaction: (i) Reaction I, semireversible uptake of triethylene melamine; (ii) reaction II, chemical interaction between triethylene melamine and intracellular thymidine mono- or triphosphate with the production of a functional analogue of the latter; (iii) incorporation of this fraudulent analogue into the newly formed DNA strand; (iv) occurrence of self-perpetuating errors in the sequence of natural bases during subsequent rounds of replication of the analogue-containing DNA strand. It is postulated that the mechanism of mutagenic responses to different types of mutagens can fit either a simplified (mutagenic base analogues) or extended version (radiation) of this schema.